Light-ion production in the interaction of 96 MeV neutrons with carbon - U. Tippawan (2018)
Double-differential cross sections for light-ion (p, d, t, He3, and α) production in carbon induced by 96 MeV neutrons have been measured at eight laboratory angles from 20° to 160° in steps of 20°. Experimental techniques are presented as well as procedures for data taking and data reduction. Deduced energy-differential, angle-differential, and production cross sections are reported. Experimental cross sections are compared with theoretical reaction model calculations and experimental data in the literature. The measured particle data show marked discrepancies from the results of the model calculations in spectral shape and magnitude. The measured production cross sections for protons, deuterons, tritons, He3, and α particles support the trends suggested by data at lower energies. © 2009 The American Physical Society.